Perlindungan Hukum terhadap Kesehatan Mental Remaja: Pentingnya Komunikasi Efektif dalam Keluarga - Kayla Andini Putri; Trini Handayani; Anita Kamilah; Aji Mulyana (UPT Publikasi Ilmiah Unisba, 2024)
ABSTRACT Adolescent mental health is becoming an increasingly pressing issue that requires serious attention, especially in the context of legal protection. This article discusses the importance of legal protection for adolescent mental health with a focus on the key role of effective communication within the family. Good communication between family members can be the first bulwark in maintaining adolescent mental health. In the context of legal protection, this article discusses various aspects, including adolescents' rights related to mental health, the importance of maintaining communication, and the role of the legal system in providing support for adolescents facing mental challenges. Through in-depth analysis, the article also highlights the implementation of policies and regulations that support the protection of adolescent mental health. The results suggest that strong legal protections can serve as a foundation to promote a holistic approach to adolescent mental health, with effective communication within the family as a key element in such protection efforts. It is hoped that this article will provide further insights into how communication within the family can support legal protections for adolescent mental health, as well as provide a basis for improving the system to better protect the rights and well-being of adolescents in the future ABSTRAK Masalah kesehatan mental remaja menjadi isu yang semakin mendesak dan memerlukan perhatian serius, terutama dalam konteks perlindungan hukum. Artikel ini membahas pentingnya perlindungan hukum terhadap kesehatan mental remaja dengan fokus pada peran kunci komunikasi efektif dalam keluarga. Komunikasi yang baik antar anggota keluarga dapat menjadi benteng pertama dalam menjaga kesehatan mental remaja. Dalam konteks perlindungan hukum, artikel ini membahas berbagai aspek, termasuk hak-hak remaja terkait kesehatan mental, pentingnya menjaga komunikasi, dan peran sistem hukum dalam memberikan dukungan bagi remaja yang menghadapi tantangan mental. Melalui analisis mendalam, artikel ini juga menjelaskan implementasi kebijakan dan regulasi yang mendukung upaya perlindungan kesehatan mental remaja. Hasilnya menunjukkan bahwa perlindungan hukum yang kuat dapat menjadi landasan untuk mendorong pendekatan holistik terhadap kesehatan mental remaja, dengan komunikasi efektif dalam keluarga sebagai elemen utama dalam upaya perlindungan tersebut. Artikel ini diharapkan dapat memberikan wawasan lebih lanjut tentang bagaimana komunikasi dalam keluarga dapat mendukung perlindungan hukum terhadap kesehatan mental remaja, serta memberikan dasar bagi perbaikan sistem yang lebih baik dalam melindungi hak dan kesejahteraan remaja di masa mendatang. Kata Kunci : Hukum; Keluarga; Kesehatan; Komunikasi; Perlindungan.